Initial training of indigenous educators in Paraná: Dialogues between the university and the indigenous territory (Revista Contexto & Educação, 2025)
This paper discusses the initial training of indigenous educators, requested by the indigenous territory of Rio das Cobras - Paraná, and developed at the Universidade Estadual do Centro-Oeste (Unicentro). It justifies that, after two decades of specific policies for the inclusion of indigenous people in higher education in Paraná, the number of trained teachers does not meet the demand of the 40 indigenous schools in the state. The paper shares and discusses elements of the experience of training indigenous educators at Unicentro. It is a qualitative research that examines the context of indigenous higher education and conducts document analysis, such as the course's political-pedagogical project. The work is based on theoretical-legal foundations. It concludes that there have been legal and judicial achievements in Brazil driven by indigenous peoples. It highlights that the project's elements seek to incorporate alternating pedagogy, bilingualism, interculturality, the production of educational materials, and mobility. It shows that the collective management and conduct between the university and the community represent an advance in the training of educators. However, it notes the limitations in implementing a specific course for indigenous peoples, such as a lack of funding, the incorporation of indigenous culture, and the need to train the trainers. It reinforces that collective decision-making and empowerment through these proposals benefited everyone. The university learned from indigenous cultures, and these cultures learned from the university's culture, which strengthens the whole process. It emphasizes the need to evaluate the role of orality in training and to train indigenous masters and doctors to incorporate them into the university faculty.
Keywords: Teacher training; Political-Pedagogical Project; Indigenous Peoples